Concurrent ibrutinib plus venetoclax in relapsed/refractory mantle cell lymphoma: the safety run-in of the phase 3 SYMPATICO study - Wang, Michael; Ramchandren, Radhakrishnan; Chen, Robert; Karlin, Lionel; Chong, Geoffrey; Jurczak, Wojciech; Wu, Ka Lung; Bishton, Mark; Collins, Graham P.; Eliadis, Paul; Peyrade, Frédéric; Lee, Yihua; et al. (Journal of hematology and oncology, 2021)
Ibrutinib plus venetoclax, given with an ibrutinib lead-in, has shown encouraging clinical activity in early phase studies in mantle cell lymphoma (MCL). The ongoing phase 3 SYMPATICO study evaluates the safety and efficacy of concurrently administered, once-daily, all-oral ibrutinib plus venetoclax in patients with relapsed/refractory MCL. A safety run-in (SRI) cohort was conducted to inform whether an ibrutinib lead-in should be implemented for the randomized portion. Patients received concurrent ibrutinib 560 mg continuously plus venetoclax in a 5-week ramp-up to venetoclax 400 mg for up to 2 years. The primary endpoint was occurrence of tumor lysis syndrome (TLS) and dose-limiting toxicities (DLTs). The SRI cohort enrolled 21 patients; six and 15 were in low- or increased-risk categories for TLS, respectively. During the 5-week venetoclax ramp-up, three patients had DLTs, and one patient at increased risk for TLS had a laboratory TLS; no additional TLS events occurred during follow-up. With a median follow-up of 31 months, the overall response rate was 81% (17/21); 62% (13/21) of patients had a complete response. SRI data informed that the randomized portion should proceed with concurrent ibrutinib plus venetoclax, with no ibrutinib lead-in. Ibrutinib plus venetoclax demonstrated promising efficacy; no new safety signals were observed. Trial registration : ClinicalTrials.gov, NCT03112174. Registered 13 April 2017, https://clinicaltrials.gov/ct2/show/NCT03112174 .